IoTCP: A Novel Trusted Computing (Journal of The Colloquium for Information Systems Security Education, 2018)
The ability to understand, predict, secure and exploit the vast array of heterogeneous network of things is phenomenal. With the ever-increasing threats to cyber physical systems and Internet of Things, security on those networks of data-gathering sensors and systems has become a unique challenge to industries as well as to military in the battlefield. To address those problems, we propose a trusted computing protocol that employs discrete Trusted Platform Modules and Hardware Security Modules for key management, a blockchain-based package verification algorithm for over-the-air security, and a secure authentication mechanism for data communication. The IoT-based Trusted Computing Protocol implements integrated hardware security, strong cryptographic hash functions, and peer-based blockchain trust management. We have tested the protocol under various circumstances where devices have built-in securities while others do not. We apply the new protocol to a SCADA system that contains more than 3,000 edge devices. The preliminary results show that proposed protocol establishes trust, improves security, integrity, and privacy.
Keywords: Trusted Computing; IoT; IoBT; Blockchain; TPM